MPM Simulations of the Interaction Between Water Jet and Soil Bed. (2017) - Liang, Dongfang; Zhao, Xuanyu; Martinelli, Mario
Abstract: In offshore engineering, pipelines are often buried in the seabed to avoid the damage caused by ocean waves, currents, fishing activities, etc . For its reliability, the high-speed water jet has been increasingly used for constructing the pipe trenches. The jet-soil interaction is a highly complicated two-phase problem. A three-dimensional Material Point Method (MPM) model, Anura3D (www.anura3d.com ), is used to simulate the jet trenching processes. In this preliminary study, the effect of the water jet speed on the trenching process is simulated. The research demonstrates the advantages of the MPM model in handling the free surface and soil-water interaction problems, and the results are useful for the offshore oil and gas industry. In future research, the different controlling parameters of the trenching operation, including the jet size, water pressure, translational speed and soil strength, will be tested to optimize the trenching operation to achieve high efficiency.